2020
DOI: 10.1051/0004-6361/202038283
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically important magnetic fields near the event horizon of Sgr A*

Abstract: We study the time-variable linear polarisation of Sgr A* during a bright near-infrared flare observed with the GRAVITY instrument on July 28, 2018. Motivated by the time evolution of both the observed astrometric and polarimetric signatures, we interpret the data in terms of the polarised emission of a compact region (“hotspot”) orbiting a black hole in a fixed, background magnetic field geometry. We calculated a grid of general relativistic ray-tracing models, created mock observations by simulating the instr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…The above-mentioned behaviour of the polarization angle at certain radius close to the black hole horizon is a signature of strong gravity. Although this provides a specific evidence which in future can help us to measure the model parameters, so far its practical use has been attempted only in a few preliminary cases with tentative results, such as the SMBH in Sagittarius A*, where the near-infrared polarimetry has been achieved from ground-based observations (Meyer et al, 2006;Shahzamanian et al, 2015;Gravity Collab. et al, 2020b), and M87 nucleus with the EHT in mm domain (Kravchenko et al, 2020).…”
Section: Polarization Angle Near Black Holementioning
confidence: 99%
“…The above-mentioned behaviour of the polarization angle at certain radius close to the black hole horizon is a signature of strong gravity. Although this provides a specific evidence which in future can help us to measure the model parameters, so far its practical use has been attempted only in a few preliminary cases with tentative results, such as the SMBH in Sagittarius A*, where the near-infrared polarimetry has been achieved from ground-based observations (Meyer et al, 2006;Shahzamanian et al, 2015;Gravity Collab. et al, 2020b), and M87 nucleus with the EHT in mm domain (Kravchenko et al, 2020).…”
Section: Polarization Angle Near Black Holementioning
confidence: 99%
“…An important EHT observing target is the black hole Sgr A* at the center of our own galaxy. The polarization of Sgr A* has significant time variability in both submillimeter [52][53][54] and near-infrared [55][56][57][58] observations, with particularly rapid variability in near-infrared flares. The flares are likely born out of various plasma and MHD effects such as magnetic reconnection [59,60].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, using infrared interferometry, the GRAVITY collaboration has recently reported the first resolved centroid motion and polarization during flares of Sgr A* [57]. Both the centroid and polarization traced loops over time, which were interpreted using a model of an orbiting equatorial hotspot [57,58]. In simulations of motion of a small Gaussian hotspot, [57] (see Appendix D therein) found that the presence of a single polarization loop in Q, U , in which the orbital period in polarization is the same as the orbital period of the hotspot, is a signature of magnetic fields perpendicular to the orbital plane (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations